FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ROKOK ELEKTRIK PADA PEROKOK PEMULADI SMA KOTA BEKASI - Ferosvi Nada Adhima El Hasna; Kusyogo Cahyo; Laksmono Widagdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on the results of the preliminary survey that conducted by the researcher by spreading questionnaires to 581 High School students in Bekasi resulting 22.3% smoke electronic cigarette with details the active novice smokers who’re using electronic cigarette in the amount of 8.3% while about 13.4% where the smokers who used to smoke tobacco cigarette are now moved on to electronic cigarette. The purpose of this research is to analyze the factors that associated with the usage of electronic cigarette to novice smokers in Bekasi City’s High School. The type of this research is descriptive analytic with quantitative approach method. The used research design is cross-sectional study, where the amount of the population in this research is 52 people who are novice electronic smokers in four Bekasi City’s High School. The Total of Population technique is used to get the sample for this research where the entire population get the chance to be the sample for the research. Data analysis includes descriptive analysis with the presentation of the frequency distribution table and the analytic analysis uses Chi-Square test to see whether there or not there the relation between respondents’ friends’ support and family’s support with the usage of electronic cigarette in Bekasi City’s High School. Statistical test results show that 67.3% respondents use electronic cigarrete. The variables related with the usage of electronic cigarette to novice smokers in Bekasi City’s High School is the availability of the electronic cigarette (p-value = 0.000), the affordability of the electronic cigarette (p-value = 0.000), and the respondents’ friends’ support (p-value = 0.016). While the respondents’ knowledge about the electronic cigarette (p-vaalue = 0.416), the respondents’ attitude to the usage of the electronic cigarette (p-value = 0.538), the respondents’ pocket money (p-value = 1.000) and the family’s support (p-value = 0,238) is not related with the usage of the electronic cigarette to novice smokers in Bekasi City’s High School.